Investigation and management of severe hyponatraemia in a hospital setting. Issue 965 (3rd March 2006) - Huda, M S B; Boyd, A; Skagen, K; Wile, D; van Heyningen, C; Watson, I; Wong, S; Gill, G
Abstract : Aims: To evaluate the assessment and management of severe hyponatraemia in a large teaching hospital. Methods: Inpatients with serum sodium <125 mmol/l were identified prospectively from a laboratory database over a six month period. Notes were examined and data extracted. Case notes were carefully reviewed retrospectively by a consultant endocrinologist with regard to accuracy of the diagnosis and the appropriateness of investigations and management. Results: 104 patients with a serum sodium <125 mmol/l were identified. Mean (SD) age was 69 (14), 52% were female, mean hospital stay was 16 (12) days, and overall mortality 27%. Adequate investigations were rarely performed. Only 28 (26%) had plasma osmolality measured, 29 (27%) urine osmolality, 11 (10%) urinary sodium, 8 (8%) plasma cortisol, and 2 (2%) a short Synacthen test. Comparing the "ward" and "specialist review" diagnoses, there were significant discrepancies for "no cause found" (49% v 27%, p<0.001), alcohol (6% v 11% p<0.01), and syndrome of inappropriate antidiuresis (20% v 32%, p = 0.001). Treatment was often illogical with significant management errors in 33%. These included fluid restriction and intravenous saline given together (4%) and fluid restriction in diuretic induced hyponatraemia (6%). Mortality was higher in the group with management errors (41% v 20% p = 0.002). Conclusion: Severe hyponatraemia is a serious condition, but its investigation and evaluation is often inadequate. Some treatment patterns seem to be arbitrary and illogical, and are associated with higher mortality.